2020
DOI: 10.1186/s12902-020-0513-x
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function mutation in the voltage-gated potassium channel gene KCNQ1 and glucose-stimulated hypoinsulinemia - case report

Abstract: Background: The voltage-gated potassium channel Kv7.1 encoded by KCNQ1 is located in both cardiac myocytes and insulin producing beta cells. Loss-of-function mutations in KCNQ1 causes long QT syndrome along with glucosestimulated hyperinsulinemia, increased C-peptide and postprandial hypoglycemia. The KCNE1 protein modulates Kv7.1 in cardiac myocytes, but is not expressed in beta cells. Gain-of-function mutations in KCNQ1 and KCNE1 shorten the action potential duration in cardiac myocytes, but their effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Kv7.1 also associates with KCNE1 in the inner ear, where they regulate auditory function and pancreatic acinar cells where activation of the Kv7.1-KCNE1 channel provides the driving force for Cl – secretion ( Kim and Greger, 1999 ; Köttgen et al, 1999 ; Warth et al, 2002 ). In addition, Kv7.1 channels in the pancreatic ß-cells contribute to the regulation of insulin secretion, and loss of function mutations in the KCNQ1 gene leads to impaired ß-cell insulin secretion, which is associated with type 2 diabetes ( Ullrich et al, 2005 ; Unoki et al, 2008 ; Yasuda et al, 2008 ; Yamagata et al, 2011 ; Liu et al, 2014 ; Torekov et al, 2014 ; Min Lee et al, 2017 ; Zhang et al, 2020 ). Furthermore, association of Kv7.1 with KCNE3 in epithelial tissues of the colon, small intestine and airways regulates the transport of water and salts ( Schroeder et al, 2000b ; Grahammer et al, 2001a , b ; Vallon et al, 2005 ).…”
Section: Camp Regulation Of Kv7 Channelsmentioning
confidence: 99%
“…Kv7.1 also associates with KCNE1 in the inner ear, where they regulate auditory function and pancreatic acinar cells where activation of the Kv7.1-KCNE1 channel provides the driving force for Cl – secretion ( Kim and Greger, 1999 ; Köttgen et al, 1999 ; Warth et al, 2002 ). In addition, Kv7.1 channels in the pancreatic ß-cells contribute to the regulation of insulin secretion, and loss of function mutations in the KCNQ1 gene leads to impaired ß-cell insulin secretion, which is associated with type 2 diabetes ( Ullrich et al, 2005 ; Unoki et al, 2008 ; Yasuda et al, 2008 ; Yamagata et al, 2011 ; Liu et al, 2014 ; Torekov et al, 2014 ; Min Lee et al, 2017 ; Zhang et al, 2020 ). Furthermore, association of Kv7.1 with KCNE3 in epithelial tissues of the colon, small intestine and airways regulates the transport of water and salts ( Schroeder et al, 2000b ; Grahammer et al, 2001a , b ; Vallon et al, 2005 ).…”
Section: Camp Regulation Of Kv7 Channelsmentioning
confidence: 99%
“…This suggests that the hypersecretion of insulin found in the setting of KCNQ1/Kcnq1 LoF is because of an effect in the beta cell itself and/or in the other endocrine cells of the pancreatic islet, but not from effects occurring outside of the pancreas. Additionally, a case study of a patient with a gain of function mutation in KCNQ1 revealed hypoinsulinaemia after an oral glucose load, further confirming K v 7.1's function in insulin secretion 54 …”
Section: The Role Of Delayed Rectifier K+ Channels In the Pancreatic ...mentioning
confidence: 75%
“…Co‐assembly with the other KCNEs either results in a constitutively open channel (KCNE2 and KCNE3) or in inhibition of the current (KCNE4 and KCNE5) 60 . In comparison to the heart, KCNE1 does not appear to be expressed in the human pancreatic beta cell, 14 and in a case report of a patient with a KCNE1 LoF mutation no changes in insulin secretion were observed 54 . It remains unclear which KCNE(s) may be co‐assembling with KCNQ1 in the pancreatic beta cell.…”
Section: Can Knowledge Of the Cardiac Function Of Kv71 And Kv111 Info...mentioning
confidence: 99%
See 1 more Smart Citation
“…KCNQ1 is also expressed in a variety of endocrine tissues such as human pancreatic beta-cells 6 , alpha-cells 7 , the gastrointestinal tract 8 and hypothalamic GNRH secreting neurons 9 . While a gain-of-function mutation in KCNQ1 was associated with reduced insulin response to oral glucose 10 LQTS patients with LoF mutations in KCNQ1 present with hyperinsulinemia and subsequent hypoglycemia after an oral glucose challenge 11 . Similar findings were made in patients with LoF mutations in KCNH2 , encoding K v 11.1 (hERG), the second most common cause of LQTS 12 .…”
Section: Introductionmentioning
confidence: 99%